Pengembangan Sumberdaya Manusia dalam Meningkatkan Kualitas Pelayanan dan Kepuasan Pelanggan (Studi pada Aparatur Pemerintah Provinsi Kalimantan - Asri, Syachrumsyah (Universitas Brawijaya, Indonesia, 2015)
The government human resources service quality needs improvement through,among others graded education, training and development according to the respectiveneeds. The increasing economic dynamics of the society requires high quality services forsocial satisfaction.It is hypothesized that: (1) Human resource development hasa positiveinfluence on service quality; (2) Human resource quality has a positive influence on servicequality; (3) Human resource quality has a positive influence on customers satisfaction; (4)Service quality has a positive influence on customers on satisfaction.Path analysis was usedfor hypotheses testing. Data were collected from KDPDPKT Samarinda branch and thesociety benefiting the services.The study result shows that all four hypotheses are confirmed.It is concluded that (1) HR development has an influence of 20,64% on HR quality; (2) HRquality has an influence of 25,56% on service quality; (3) HR quality has an influence of39,42% on customers satisfaction; and (4) Service quality has an influence of 64,00% oncustomers satisfaction. This implies that education, training and development influencegovernment HR quality which further influences the government institutions performanceswhich are realized through service quality to the society. The higher the service quality, thehigher the customers satisfaction.